Re-visioning Curriculum and Pedagogy in a University Science and Technology Education Setting: Case Studies Interrogating Socio-Scientific Issues - Overson Shumba; George Kasali; Yaki Namiluko; Beauty Choobe; Gezile Mbewe; Moola Mutondo; Kenneth Maseka (Environmental Association of Southern Africa, 2016)
We present reflections on case studies in which a team of researchers and student researchers at the Copperbelt University in Zambia carried out real-world context investigations. The case studies involve estimating the greenhouse gas emissions associated with activities in the university, exploring agro-applications of biotechnologies, investigating chemical pollutants that are potential endocrine disruptors in the environment and in fish, and modelling how to mainstream the socio-scientific issues into curriculum and pedagogy for science educators and teachers. The analysis using the lenses of education for sustainable development (ESD) and 'learning as connection' lead to the suggestion of re-visioning curriculum and pedagogy. This re-visioning entails that the learning of the technical content of science subjects is balanced with a consideration of socioscientific issues and ESD processes. Project-based learning provided the model for integrating the concepts and principles of ESD and 'learning as connection' into the curriculum and pedagogy.